"Just Perceiv'd & Next Door to Nothing:" an Investigation of Minima in the Work of George Berkeley - (:unkn) unknown (My University, 2013)
For George Berkeley the minimum visibile and the minimum tangibile are the minimum points that can be perceived by the senses of sight and touch (NTV 54). His account of minima is considered by some to be central to his account of perception and his assault on skepticism, while others view the account as simply a digression from his main theme in the New Theory of Vision. One issue in particular that commentators disagree on is whether or not Berkeley understands minima to be extended or not extended. I argue that minima can only be understood as not extended. In order to do this I use an argument very similar to one presented by David Hume. I conclude by considering why Hume uses the argument and Berkeley doesn't.
Keywords: David Hume; George Berkeley; Minima; Perception